Handbook of research on multimedia cyber security - Gupta, Brij, d 1982; Gupta, Deepak, d 1983 (A volume in the advances in information security, privacy, and ethics (AISPE) book series, 2020)
"This book explores recent and future advancements in multimedia security and processing. It also presents new and recent algorithms in various emerging areas for copyright protection, content authentication, ownership authentication, and identity theft"--